Elements for a sociology of institutions:: ¿A black box of politics in Ecuador? - Herrera, Miguel (2022)
The study of political institutions occupies an unequal place in the social sciences in Ecuador. On the one hand, institutions have been and are central to the analysis of the Ecuadorian State and politics, with numerous contributions exposing their history, modes of organization and operation, as well as the rules and formal arrangements that govern them. The literature related to the topic contains valuable contributions regarding democracy and governance in Ecuador. On the other hand, there is still a need to explore new questions about the way in which institutions operate from the inside. The article thus presents analytical elements for the sociological approach to institutions, highlighting the contribution of a look oriented towards the actors that inhabit them and the practices they carry out.